Revitalizing Mosques Across the Ages: Historical Roles, Contemporary Issues, and Post-Pandemic Empowerment Strategies - Tandos, Rosita (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
Mosques are vital faith-based organizations (FBOs) that significantly contribute to the spiritual, social, educational, and economic welfare of communities—not only in Muslim-majority countries but also in regions where Muslims are minorities. While traditionally centered on worship, mosques today have evolved into multi-functional institutions that address diverse community needs. This study examines the historical roles of mosques from the era of the Prophet Muhammad (pbuh) through the Caliphates to the modern era, highlighting current challenges and strategies for empowerment, particularly in the context of the COVID-19 pandemic. Using a qualitative approach, data were collected from 425 participants across eight prominent mosques in major Indonesian cities through surveys, observations, interviews, and secondary sources. Key findings reveal that mosques play an essential role in promoting moderate Islam, social cohesion, and inclusive community services. During and after the pandemic, mosques adapted by expanding digital outreach, enhancing women's participation, and launching economic and health initiatives. The study underscores the strategic importance of revitalizing mosques as inclusive, resilient institutions that foster both religious devotion and community empowerment. Insights from the Istiqlal Mosque in Jakarta demonstrate best practices that may inform mosque development globally.